Some Questions of Parole in the Criminal Law of the Russian Federation - Tarhanov, Ildar A.; Gayfutdinov, Ramil R.; Karimov, Adel M.; Muzafarov, Ilnur A. (Cuestiones Políticas, 2020)
The article examined fundamental issues of parole in the criminal law of the Russian Federation and, at the same time, aspects of the negative deloscope impact on the identity of the inso, from various points of view on the "social elevators" programme. All these social problems cause a low level of voluntary softening of the damage caused to the victim. During the analysis, we found that the legislature did not formulate well the model that it behaves encouraging to compensate for the damage caused, as set out in the standard text. An indication of the possibility of using incentives in the event of damages the possibility of an ambiguous interpretation of the standard text, leading to difficulties in law enforcement. In the conclusions, we express our position on the need for legal regulation other than this issue. Particular attention was paid to the victim's role in determining the amount of damage. The input of the article focused on discussing various approaches to this issue and establishing the need to clarify the criminal legal status of the victim at the level of the plenary session of the Supreme Court of the Russian Federation.